Pembuatan Dan Penggunaan Jamu "Semua Terhindar Penyakit" Di Desa Tangkil Sentul Kab Bogor - Malaha, Naomi; Sima, Yenni; Samila, Samila; Prihatini, Surya; Rahmawati, Agustini Liviana Dwi; Marpaung, Mauritz Pandapotan (Barongko: Jurnal Ilmu Kesehatan, 2025)
Herbal medicine is a traditional concoction as one of the widely known and utilized treatment efforts by the community with the aim of treating minor illnesses, preventing the onset of illness, maintaining endurance and health of the body. The purpose of this study was to obtain information about the manufacture and use of herbal medicine so that the community is in a healthy condition "all are free from disease". This research method is a non-experimental study with a pretest and posttest design using an instrument in the form of a questionnaire. The results of the study showed that the majority with an average before drinking herbal medicine stated yes (50.3%) and no (49.7%) while those who consumed herbal medicine before answered yes (76.35%) while those who did not (23.7%). The conclusion that there was an increase in the percentage that was previously quite good because respondents felt the benefits for respondents from the herbal medicine and the results obtained by respondents after drinking herbal medicine gave a good response and their perception after consuming herbal medicine is known to have been passed down from generation to generation to make the body healthy and fit and increase body immunity.